Impact of Self-Efficacy and Work Discipline on Employee Performance in Sociopreneur Initiatives - Lestari, Sri; Watini, Sri; Rose, Dhiyah Eloise (Aptisi Transactions On Technopreneurship (ATT), 2024)
Understanding the determinants of employee performance is crucial for achieving organizational success. This study investigates how self-efficacy and work discipline affect employee performance at Panti Sasana Tresna Werdha RIA Pembangunan. Using a full sample of 50 employees, the research employed various analytical techniques, including tests for validity, reliability, normality, multicollinearity, and heteroscedasticity, as well as multiple linear regression, correlation analysis, F tests, and T-tests. The T-test results indicated that both self-efficacy (t-count 2.056 > t-table 2.012, p < 0.05) and work discipline (t-count 4.868 > t-table 2.012, p < 0.05) have significant positive effects on employee performance. The multiple correlation analysis demonstrated a strong positive relationship between self-efficacy, work discipline, and employee performance (correlation coefficient 0.844). The coefficient of determination (R²) was 0.713, showing that these two factors account for 71.3% of the variance in employee performance, with the remaining 28.7% attributed to other variables not included in this study, such as work motivation, compensation, work environment, and leadership. These findings indicate that boosting self-efficacy and reinforcing work discipline are essential for enhancing employee performance. Therefore, organizations should invest in comprehensive training and development programs to cultivate these qualities and maintain high performance levels among their staff.